Adjuvant rituximab therapy in pemphigus: a single-center experience of 18 cases. (December 2013) - Baum, Sharon; Gilboa, Sarit; Greenberger, Shoshana; Pavlotsky, Felix; Trau, Henri; Barzilai, Aviv
Background: Pemphigus vulgaris (PV) follows a chronic relapsing course where the mainstay of therapy has been oral corticosteroids and second-line immunosuppressive and immunomodulating therapies. Successful responses have been reported with rituximab, a chimeric monoclonal anti-CD20 antibody targeting B lymphocytes, although its use in recalcitrant pemphigus is still being studied. Methods: A retrospective analysis is presented of 18 patients with cutaneous and mucous membrane involvement after disease relapse following steroid and other adjuvant therapies who were treated with rituximab (4 intravenous infusions of 375 mg/m2 once weekly for 4 consecutive weeks). Results: At 3 months follow-up, 44% (8/18) of cases achieved complete disease remission with a further 44% (8/18) showing partial remission. Further follow-up showed 5/8 partial responders achieving a complete response with 4 cases experiencing disease relapse (72% response at 9 months). There were no adverse drug-related events and its use resulted in a significant reduction in steroid dosage during follow-up. Conclusion: Rituximab is beneficial in the management of refractory PV, resulting in clinical remission and a steroid-sparing effect. Further study needs to examine rituximab dosage and scheduling as well as its place within the treatment algorithm.